2019
DOI: 10.20529/ijme.2018.041
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound in rural India: a failure of the best intentions

Abstract: The Pre-Conception and Pre-Natal Diagnostic Techniques Act was written to prevent societally unacceptable harms including intentional sex selection. The pragmatism required to enforce this law has profound effects on the ability of rural Indians to access diagnostic ultrasonography. In so doing, it may have inadvertently placed a heavier burden on the poorest and worsened health inequity in India, creating serious ethical and justice concerns. It is time to re-examine and update the law such that diagnostic ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…USG were done during camps at PHCs and Sub-District Hospital (SDH) and women did not know details of abnormalities. Phutke et al reported it is essential to re-examine and update the use of diagnostic, USG widely available even the most peripheral health facilities [10]. Studies showed that pregnant women generally value routine ultrasounds in the first two trimesters because they get reassurance and chances to see their unborn baby.…”
Section: Discussionmentioning
confidence: 99%
“…USG were done during camps at PHCs and Sub-District Hospital (SDH) and women did not know details of abnormalities. Phutke et al reported it is essential to re-examine and update the use of diagnostic, USG widely available even the most peripheral health facilities [10]. Studies showed that pregnant women generally value routine ultrasounds in the first two trimesters because they get reassurance and chances to see their unborn baby.…”
Section: Discussionmentioning
confidence: 99%
“…Despite numerous interventions by the government and social organisations, our country has persistently observed skewed sex ratios over the years. [ 10 11 ] One of the regulations for curbing this menace was the Pre-Natal Diagnostic Technique (PNDT) act of 1994 which was amended in 2003 to the PCPNDT act.…”
Section: Female Foeticide In Indiamentioning
confidence: 99%
“…[ 3 ] Due to the apparent ineffectiveness of this law to improve sex ratios over the years, an amendment to the act was made in 2003 which incorporated USG clinics into the ambit of this law. [ 4 11 12 ] Under this law, all centres which have any equipment (including USG) which can potentially detect sex of foetus pre-conception or pre-natal have to be registered with the appropriate authorities and could be penalised for taking part or being involved in sex determination of foetus. [ 4 5 ] The families of pregnant woman who ask for sex determination are also liable to be punished.…”
Section: The Pcpndt Actmentioning
confidence: 99%
See 1 more Smart Citation
“…However, tele-ultrasound has a very limited role till date in India due to the Pre-Conception and Pre-Natal Diagnostic Techniques Act (PCPNDT Act), which requires radiologists and trained obstetricians to register their own ultrasound machines and they have to be physically present. 4…”
mentioning
confidence: 99%